Paradigmas de racionalidade e as decisões do STF nas questões relativas à base de cálculo do imposto de renda - pessoa jurídica - Renck, Renato Romeu (2006)
This doctoral dissertation aims at checking if the Brazilian Supreme Court uses recurrent paradigms, determined from a specific and defined nucleolus of intelligibility, when judging parts involved in quantifying the tax base of the income tax for legal person. The Constitution through the concept of income, establishes limits to the taxing power which must be observed in order not to risk constitutional violation. To formulate such limits, it is paramount the formulation of a verifying procedure of what income means, to confront it with the standards determined by law. Through the jurisprudence research, structuring and reasoning of judicial theses, we want to investigate if the Supreme Federal Court establishes such limits. This reasoning must be present in decision making paradigms justified by rational criteria and accepted by the judicial community. We refute the structure of rationality which justifies the theory of the national tributary law by pointing out its flaws. We use the Hermeneutic Phenomenology which is the most adequate theory to the application of the institutional regulations and it also allows for the inference of the universal tributary concepts into single concepts. It defines the limits of each individual taxation. From the results of this research the following is justified: when the Supreme Court rejects as several judged antecedents and permits that the income be determined by the legislator, it is not taking into account the formation of a judging paradigm for the evaluation of income. As it states that the legislator has autonomy to determine what tribute income is for the legal person, the Federal Supreme Court renounces the constitutional duty to establish an applicable paradigm to the income evaluation procedure which institutes the limits to the power of tribute. Such renunciation empowers the legislator to institute whatever pleases him or her, removing from the context of the income tax any remains of the existence of the Rule of Law